Strengthening of Hollow Square Sections under Compression Using FRP Composites. (22nd February 2014) - Sundarraja, M. C.; Sriram, P.; Ganesh Prabhu, G.
Abstract : The feasibility study on carbon fibre reinforced polymer (CFRP) fabrics in axial strengthening of hollow square sections (HSS) was investigated in this paper. CFRP was used as strips form with other parameters such as the number of layers and spacing of strips. Experimental results revealed that the external bonding of normal modulus CFRP strips significantly enhanced the load carrying capacity and stiffness of the hollow sections and also reduced the axial shortening of columns by providing external confinement against the elastic deformation. The increase in the CFRP strips thickness effectively delayed the local buckling of the above members and led to the inward buckling rather than outward one. Finally, three-dimensional nonlinear finite element modeling of CFRP strengthened hollow square sectionswas created by using ANSYS 12.0 to validate the results and the numerical results such as failure modes and load deformation behaviour fairly agreed with the experimental results.